2016
DOI: 10.1534/genetics.116.189258
|View full text |Cite
|
Sign up to set email alerts
|

Control of Formin Distribution and Actin Cable Assembly by the E3 Ubiquitin Ligases Dma1 and Dma2

Abstract: Formins are widespread actin-polymerizing proteins that play pivotal roles in a number of processes, such as cell polarity, morphogenesis, cytokinesis, and cell migration. In agreement with their crucial function, formins are prone to a variety of regulatory mechanisms that include autoinhibition, post-translational modifications, and interaction with formin modulators. Furthermore, activation and function of formins is intimately linked to their ability to interact with membranes. In the budding yeast Sacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 106 publications
1
11
0
Order By: Relevance
“…Regulation of cytoskeletal structures by the ubiquitin-proteasome system is an emerging regulatory mechanism (Deng and Huang, 2014). However, most previous studies have used yeast or cultured cells (Wang et al, 2003;Chen et al, 2009;Razinia et al, 2011Razinia et al, , 2013Juanes and Piatti, 2016;Girouard et al, 2016;Wu et al, 2018). Our work is one of few examples to date detailing the mechanism by which the UPS organizes and remodels a cytoskeletal structure in a metazoan developmental model system.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of cytoskeletal structures by the ubiquitin-proteasome system is an emerging regulatory mechanism (Deng and Huang, 2014). However, most previous studies have used yeast or cultured cells (Wang et al, 2003;Chen et al, 2009;Razinia et al, 2011Razinia et al, , 2013Juanes and Piatti, 2016;Girouard et al, 2016;Wu et al, 2018). Our work is one of few examples to date detailing the mechanism by which the UPS organizes and remodels a cytoskeletal structure in a metazoan developmental model system.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies need to investigate the number and arrangement of ubiquitin moieties on VASP and how ubiquitination of VASP alters its function on the molecular level or changes the state of the tetramer. Such work could have intriguing implications for the regulation of other actin-associated proteins that function as multimers, such as formins, which recent work has suggested are also regulated by nondegradative ubiquitination (Juanes and Piatti, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that Ali1 interacts with multiple ubiquitination proteins, including E1, E2, and E3 proteins, particularly in TC conditions (73). Ubiquitination is most often considered in the context of proteasomal degradation, but it can also direct diverse subcellular localizations (74–76).…”
Section: Discussionmentioning
confidence: 99%